The Collapse of an Empire and the Restructuring of the Global Financial System; The Rise of China and the Implications for Macroeconomic Theory. - Smith, Frazer J (2011)
This study provides an in-depth analysis into the political and economic drivers behind the financial crisis of 2008-2009. The purpose of which is to consider these factors in a global economic context and to provide an informed perspective of the impact of these events. This is taking into consideration the shifting power balance between Western advanced economies and the rapid growth of East Asian and other emerging markets, most significantly China. Additionally, this aims to question whether the current Western free-market model is sustainable as a path to competitive growth in spite of excessive deficit spending and to question the nature of reform that is apparently needed.